Sick of my parents? Consequences of parental ill health on adult children - Anna Norén (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
I study the consequences for labor market outcomes and sick leave of having an elderly parent in need of care. Using Swedish register data I compare the labor market outcome trajectories of adult children before and after their parent suffers a health shock. I find that employment and income of adult children are slightly reduced in the years leading up to the demise of their parent, but that the size of the impact is largest in the year, and the year after, parental demise. I also find that daughter's sick leave absence increases in the year that the parent dies. No effects on labor market outcomes are found from having a parent suffering stroke. Furthermore, I find no clear gender differences between sons and daughters in the impact of having a parent with increased care demand. Taken together, the results suggest that the opportunity costs of parental care need in the form of adverse labor market impacts are small.
Keywords: J14; J22; 330; Formal and Informal care; Elderly; Labor supply